2015
DOI: 10.1007/s11105-015-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BrCIPK1 Gene Enhances Abiotic Stress Tolerance by Increasing Proline Biosynthesis in Rice

Abstract: The calcineurin B-like protein (CBL)-CBLinteracting protein kinase (CIPK) pathway is emerging as a major signaling pathway in plants. To understand the function of CIPK, the gene named BrCIPK1 from Brassica rapa were introduced into rice. Characterization of BrCIPK1 gene showed a 1982 bp, containing 1509 bp coding region and 502 amino acids. Green fluorescent protein (GFP)-tagged BrCIPK1 was observed exclusively in the cytoplasmic and peripheral regions in the plant cell. Gene expression showed that its messen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Alkaline stress and salt stress are often interconnected and may induce mixed effects, such as osmotic, specific ion and high-pH effects, and therefore are difficult to control and engineer 34 36 . Studies have used stress-responsive genes to improve the resistance of rice to adverse environments by gene transformation 37 39 , and many genes are involved in the responses of rice to various abiotic stresses 40 43 . Studies in recent years have provided valuable information on the molecular mechanisms for stress resistance in plants based on morphological, physiological and molecular responses.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline stress and salt stress are often interconnected and may induce mixed effects, such as osmotic, specific ion and high-pH effects, and therefore are difficult to control and engineer 34 36 . Studies have used stress-responsive genes to improve the resistance of rice to adverse environments by gene transformation 37 39 , and many genes are involved in the responses of rice to various abiotic stresses 40 43 . Studies in recent years have provided valuable information on the molecular mechanisms for stress resistance in plants based on morphological, physiological and molecular responses.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, the concentration of proline was remarkable increased during drought stress (Mostajeran & Rahimi-Eichi, 2009). Abdula et al (2016) found that the increasing of proline biosynthesis enhanced abiotic stress tolerance in rice varieties. However, Bing-Sheng et al (2014) suggested that proline accumulation is not correlated with salt, alkaline and osmotic stresses in rice.…”
Section: Introductionmentioning
confidence: 99%
“…In maize, ZmCIPK8 is involved in plant responses to drought and other abiotic stresses by regulating stress-related genes (Tai et al, 2016). The expression of the P5CS1 gene is regulated by OsCIPK1, enhancing production of proline which acts as a cryoprotectant during cold stress and as osmolyte during drought stress in rice (Abdula et al, 2016). Both wheat TaCIPK2 and Stipa purpurea SpCIPK26 positively regulate the expression CAT genes, thereby negatively modulating H 2 O 2 content Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%